ARTIFICIAL INTELLIGENCE (AI) IN THE DIAGNOSIS OF PATHOLOGIST-CONFIRMED LUNG CANCER: A SYSTEMATIC REVIEW AND A DIAGNOSTIC TEST ACCURACY (DTA) META-ANALYSIS - Maren Irgiwi Fadlilah; Wijaya Hadi Suryanto (International Medical Journal Corp. Ltd, 2025)
Objectives Lung cancer continues to be the primary cause of cancer-related deaths globally, with early detection essential for enhancing survival rates. Notwithstanding progress in imaging and pathology, existing diagnostic techniques encounter constraints including elevated false-positive rates, inter-observer variability, and difficulties in detecting smaller, early-stage nodules such as ground-glass nodules (GGNs). Artificial Intelligence (AI) provides prospective answers by improving diagnostic accuracy and efficiency. The objective of this study is to assess the efficacy of AI algorithms in diagnosing pathologist-confirmed lung cancer, emphasizing their diagnostic accuracy and potential to transform clinical practice. Methods A systematic review and meta-analysis were performed in accordance with PRISMA recommendations. A thorough literature search was conducted utilizing the Cochrane Library and PubMed until May 7, 2025, employing keywords pertinent to lung neoplasms and artificial intelligence. The inclusion criteria targeted research utilizing AI for the diagnosis of lung cancer, emphasizing diagnostic accuracy as the principal outcome. Data were extracted and evaluated for quality, and a meta-analysis was performed using Review Manager version 5.4, utilizing random-effects models to address clinical heterogeneity. Results The meta-analysis comprised six investigations with an aggregate sample size of 486 participants. AI methods, including Support Vector Machines, Random Forests, Artificial Neural Networks, and Computer-aided Diagnosis systems, had an overall sensitivity of 79.0% and specificity of 80,2%. The positive predictive value was 68.9%, while the negative predictive value was 87,3%, signifying a high reliability of negative test outcomes. AI algorithms have considerable expertise in diagnosing lung cancer, with the potential to augment early detection and increase patient outcomes. Standardizing AI models and integrating unpublished data may augment the robustness of forthcoming analyses. Conclusion AI possesses significant potential to enhance lung cancer diagnosis, providing advantages for both patients and healthcare professionals. Notwithstanding current obstacles, continuous research and development, coupled with meticulous application in clinical settings, may result in substantial progress in the early identification and therapy of cancer.